Using interference effects for controlled light propagation in four-waveguide directional couplers. Issue 19 (28th October 2017) - Evangelou, Sofia
Abstract: We explore interference effects that lead to interesting phenomena in arrays of four circularly coupled waveguides. These phenomena are shown by analytical solutions of the coupled mode equations and are verified by numerical solutions of the same equations. The interference is realized by proper design of the waveguides structure such that the propagation and the coupling constants obey specific conditions. We show that interference effects may lead to interesting phenomena, such as controlled light transfer as well as light trapping due to destructive interference.